Stres a wypalenie zawodowe wśród pielęgniarek psychiatrycznych - Popiela-Piętka, Anna (My University, 2012)
Niniejsza praca ma charakter teoretyczno-empiryczny. Realizowany program badawczy koncentruje się na analizie stresu i wypalenia zawodowego wśród pielęgniarek psychiatrycznych. Badania przeprowadzone zostały w maju i czerwcu 2012 roku wśród personelu pielęgniarskiego. W badaniu uczestniczyło 40 pielęgniarek pracujących na oddziałach psychiatrycznych: stacjonarnym i dziennym w V Wojskowym Szpitalu Klinicznym w Krakowie. Badania przeprowadzone były w sposób anonimowy i dobrowolny. Każdy badany był informowany o celu badania. Osoby badane otrzymały ankietę i wypełniły ją samodzielnie. Na podstawie otrzymanych wyników stwierdza się, iż duży odsetek wypalonych zawodowo pielęgniarek posiada zwiększoną podatność na stres oraz szczególnie odczuwa niski status zawodowy.

This thesis has theoretical and empirical character. The implemented research programme concentrates on the analysis of the stress and the professional burnout syndrome among psychiatric nurses. The survey was conducted in May and June 2012 among the nursing staff. Forty nurses took part in the survey, all of them working on the psychiatric wards: stationary and daily ward in 5th Military Hospital with Polyclinic in Cracow. The survey was anonymous and voluntary. All of the subjects were informed about the aim of the survey. Test subjects were given a questionnaire to fill it in on their own. Considering the results of the survey one can notice that a lot of nurses with professional burnout syndrome have increased susceptibility to stress. They are also particularly frustrated by their low professional status.
Stress and professional burnout syndrome among psychiatric nurses
Keywords: wypalenie zawodowe; stres; pielęgniarka psychiatryczna; osobowość; professional burnout syndrome; stress; psychiatric nurse; personality